LFP / MXene / C composite materials and their preparation and application
NanoLFP particles were grown in situ between MXene layers by solvent thermal synthesis and coated with carbon coating on their surface to construct a porous layered conductive network structure of LFP/MXene/C composite material, and solved the solution of LiFePO4 nanostructured materials and LiFePO4 The /C composite materials have problems of particle agglomeration and insufficient conductivity during the preparation process, achieving better electrochemical and low-temperature performance.
Patent Information
- Application Number
- CN202211121864.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-09-15
AI Technical Summary
The existing LiFePO4 nano-based materials and LiFePO4/C composite materials have problems of particle agglomeration and insufficient conductivity during the preparation process, resulting in poor low-temperature performance and poor electrochemical performance.
LFP/MXene material was prepared by solvent-thermal synthesis, and the surface was coated with a carbon coating to form an LFP/MXene/C composite material. This method constructs a porous hierarchical conductive network structure of "point-plane-point" by growing nano-LFP particles in situ between MXene layers.
The conductivity of the material and the lithium ion diffusion path are significantly improved, the electrochemical performance is enhanced, including improved cycle stability and rate performance, and the low temperature performance is improved.
Smart Images

Figure CN115513428B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries and relates to the preparation and application of positive electrode materials for lithium-ion batteries, and specifically relates to an LFP / MXene / C composite material and the preparation and application thereof. Background Art
[0002] For lithium-ion batteries, the cathode material accounts for the largest proportion of the battery cost, and its performance is also the main factor determining the overall electrochemical performance and safety of the battery. Lithium iron phosphate (LiFePO4) cathode material is an olivine structure with a specific capacity of 170mAh g -1 , with LiNi x Co y Mn 1-x-y Compared with O2 (NCM) materials, it has the advantages of low cost, high safety and good cycle performance. However, the limitation of LiFePO4 is its low conductivity (10 -9 ~10 -10 S cm -1 ) and low Li + Ion diffusion coefficient (10 - 14 cm 2 S -1 ), resulting in poor low temperature performance. In order to improve the electrochemical performance of LiFePO4, researchers mainly improve its performance by reducing the size of LiFePO4 particles and coating the surface of LiFePO4 with conductive carbon materials.
[0003] Current research suggests that the diffusion direction of lithium ions in LiFePO4 is one-dimensional along the b axis. Therefore, reducing the particle size of the material can shorten the diffusion distance of lithium ions during the charge and discharge process, thereby improving the rate performance of the material. Alsamet et al. synthesized nanosized LiFePO4 using the sol-gel method and hydrothermal method. The results show that the size of LiFePO4 prepared by this method can be reduced from 300-500nm to 150-350nm, and its discharge specific capacity at a current density of 0.2C is 126mAhg -1 When the current density increases to 3C, the discharge capacity reaches 70mAhg -1. LiFePO4 nano-sizing can reduce the ion and electron transmission paths and improve its electrochemical activity, but nanomaterials are prone to agglomeration during the preparation process, and the tap density is reduced. Therefore, coating the surface of LiFePO4 with a carbon coating is also the most effective way to improve the electrical conductivity of the material. The main reasons are: (1) In the preparation of LiFePO4 composite materials, the carbon source can act as a reducing agent to prevent the formation of trivalent iron; (2) The carbon coating can isolate individual LiFePO4 particles from each other and prevent further growth of the particles. (3) The carbon coating can promote the migration of lithium ions and electrons and improve the conductivity of the material. Shi et al. used a unique copolymer carbon source to prepare LiFePO4 / C composite materials. The carbon-modified LiFePO4 / C material has a higher initial discharge specific capacity (165.3 mAhg at 0.2C). -1 ), excellent rate performance (78.9 mAhg at 30C) -1 ) and good cycle stability, which can still maintain 98% of the discharge capacity after 100 cycles at 0.2C. However, the LiFePO4 / C composite material still has the problem of LiFePO4 particle agglomeration during the preparation process, which in turn affects the rate performance of the material.
[0004] MXene is a graphite-like two-dimensional layered transition metal carbide material, which is mainly obtained by etching the ceramic phase precursor MAX material. The unique two-dimensional layered structure of MXene gives it excellent electrical conductivity (2140S cm -1 ) and a large specific surface area. At the same time, due to its special elemental composition and surface functional groups, MXene exhibits excellent properties in mechanical strength, oxidation resistance, chemical stability, etc., and has been widely used as a material for energy storage devices. Summary of the invention
[0005] The purpose of the present invention is to provide a LFP / MXene / C composite material and its preparation and application in view of the shortcomings of the above-mentioned existing LiFePO4 nanomaterials and LiFePO4 / C composite materials. The present invention adopts solvent thermal synthesis of LFP / MXene material, and further obtains LFP / MXene / C composite material by coating with carbon coating. The synthesis schematic diagram is shown in FIG. Figure 1 As shown in the figure. LFP nanoparticles grow uniformly and densely between MXene layers, forming a "surface-point-surface" porous hierarchical conductive network structure. This structure can significantly improve the conductivity of the material, reduce the diffusion path of lithium ions, and provide more diffusion channels to ensure sufficient electrolyte contact. At the same time, it is also beneficial to alleviate the agglomeration and volume change of LFP nanoparticles during the charge and discharge process, thereby further improving the electrochemical performance of the material.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] <First aspect>
[0008] The present invention provides an LFP / MXene / C composite material, which has a porous hierarchical conductive network of "point-surface-point" formed by in-situ growth of nano-LFP particles between accordion-shaped MXene layers; nano-LFP particles are also grown on the surface and side of the MXene material, and the surface of the LFP / MXene is coated with a carbon layer.
[0009] <Second Aspect>
[0010] The present invention provides a method for preparing an LFP / MXene / C composite material, which comprises synthesizing an LFP / MXene material by solvent thermal method, and further coating the LFP / MXene / C composite material with a carbon coating.
[0011] As an embodiment of the present invention, the method comprises the following steps:
[0012] S1, lithium source, phosphorus source, MXene and iron source undergo hydrothermal reaction in the presence of a solvent to obtain LFP / MXene material;
[0013] S2. Add LFP / MXene material to the carbon source solution and stir the reaction at a constant temperature; the reaction product is calcined under an inert atmosphere to obtain LFP / MXene / C material.
[0014] As an embodiment of the present invention, LiOH·H2O, FeSO4·7H2O and H3PO4 are selected as lithium source, iron source and phosphorus source respectively according to the stoichiometric ratio, and the stoichiometric ratio includes 3:1:1 and the like.
[0015] As an embodiment of the present invention, the solvent includes one or both of ethylene glycol and polyethylene glycol.
[0016] As an embodiment of the present invention, step S1 specifically includes:
[0017] S1-1, a lithium source is dissolved in ethylene glycol, and a phosphorus source is added to obtain solution A;
[0018] S1-2, MXene and iron source are dispersed in ethylene glycol to obtain solution B;
[0019] S1-3. Solution B is added dropwise into solution A, and LFP / MXene material is obtained by hydrothermal reaction.
[0020] As an embodiment of the present invention, in step S1, the mass ratio of MXene to iron source is 0.01-0.10:1.66. The MXene content affects the combination of LFP and MXene. When the MXene content is low, the nano-LFP particles are all coated on the surface of the layered MXene; as the MXene content increases, nano-LFP particles will grow evenly between the layers and on the sides of the accordion-shaped MXene material to form a porous hierarchical structure, further inhibiting the self-stacking of the material, and providing more active sites, thereby improving the electrochemical properties of the material. The test results show that when the MXene content in LFP / Mxene is 7%, LFP / MXene achieves the best performance. After 100 cycles at a current density of 0.1C, the reversible specific capacity is 141.1mAh g -1 , the capacity retention rate is 96.0%.
[0021] As an embodiment of the present invention, in step S1, the temperature of the hydrothermal reaction is 160-200° C., and the time is 8-12 hours. In some embodiments, the temperature of the hydrothermal reaction is 180° C., and the time is 10 hours.
[0022] As an embodiment of the present invention, in step S1, the MXene is prepared by a method comprising the following steps:
[0023] A1, Ti3AlC2 powders are added to HF solution and etched under magnetic stirring at room temperature; after the reaction is completed, centrifugal washing is performed until pH>6, and vacuum drying is performed to obtain Ti3C2 material; each gram of Ti3AlC2 powder corresponds to 10ml of 40% HF solution;
[0024] A2. Add 10 ml of TMAOH per gram of Ti3C2 material and stir at room temperature for 12-24 hours. Centrifuge, collect the precipitate, sonicate, and centrifuge to collect the supernatant to obtain a MXene dispersion.
[0025] In step A1, the etching time is 24-36 hours. The vacuum drying is performed at 80° C. for 10-12 hours.
[0026] In step A2, the ultrasonic power is 80-120 W, preferably 100 W, and the ultrasonic time is 2-4 h.
[0027] As one embodiment of the present invention, the MXene is a modified MXene, which is prepared by a method comprising the following steps:
[0028] B1. Melamine is dispersed in anhydrous ethanol, stirred at room temperature, concentrated hydrochloric acid is added, stirring is continued, and excess solvent is removed by centrifugation. After completion, the obtained material is vacuum dried to obtain H+-modified melamine, which is recorded as H+-Melamine;
[0029] B2. Take 1 mg / ml MXene colloidal solution, recorded as solution A; H+-modified melamine is dissolved in 0.1M dilute hydrochloric acid solution, recorded as solution B; slowly add solution B to solution A, stir at room temperature to allow H+-modified melamine to be fully adsorbed in the structure of MXene, filter and wash with water, and freeze-dry to obtain black MXene-Melamine powder;
[0030] B3. The MXene-Melamine powder is kept at 500-600° C. for 2-6 hours under a nitrogen atmosphere to obtain a modified MXene material.
[0031] In some embodiments, the preparation of the modified MXene comprises:
[0032] B1. Disperse 10g of melamine in 20ml of anhydrous ethanol, stir for 1h at room temperature, add 10ml of concentrated hydrochloric acid, continue stirring for 1h, centrifuge to remove excess solvent, and after completion, place the obtained material in a vacuum oven at 80℃ to obtain H+-modified melamine, recorded as H+-Melamine;
[0033] B2. Take 50 ml of 1 mg / ml MXene colloidal solution, recorded as solution A; weigh 0.25 g H+-modified melamine according to the mass ratio of 1:5 and dissolve it in 50 ml of 0.1 M dilute hydrochloric acid solution, recorded as solution B; slowly add solution B to solution A, stir at room temperature for 1 hour to allow the H+-modified melamine to be fully adsorbed in the structure of MXene, filter and wash with water, and freeze-dry to obtain black MXene-Melamine powder;
[0034] B3. The MXene-Melamine powder was kept at 550° C. for 4 h under a nitrogen atmosphere to obtain a modified MXene material.
[0035] As an embodiment of the present invention, in step S2, the carbon source solution includes 0.2 g / ml dopamine hydrochloride aqueous solution, ethylene glycol or ascorbic acid.
[0036] As an embodiment of the present invention, in step S2, the inert atmosphere includes argon or a mixture of argon and hydrogen.
[0037] As an embodiment of the present invention, in step S2, the temperature of the constant temperature stirring reaction is 90° C., and the reaction time is 6-8 hours.
[0038] As an embodiment of the present invention, in step S2, the calcination temperature is 650-750°C, and the calcination time is 4-8h.
[0039] <Third Aspect>
[0040] The application of LFP / MXene / C composite materials in the preparation of lithium-ion battery positive electrodes also falls within the scope of protection of the present invention.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1) The key to the present invention is to directly grow nano lithium iron phosphate particles in situ within the material structure of MXene. On the one hand, the appropriate layered structure can effectively alleviate the agglomeration of nano LFP particles, and the accordion-shaped MXene can also provide a fast ion-electron conductive channel, accelerating the rapid transport of electrons and lithium ions; on the other hand, nano LFP particles grow in situ between MXene layers, forming a porous hierarchical conductive network similar to "point-surface-point"; this structure is not only conducive to increasing the contact area between the material and the electrolyte and promoting the rapid transfer of ions, but also provides more active sites for redox reactions, thereby further improving the material's cycle stability and high-rate performance.
[0043] 2) The modified MXene obtained by the present invention; Structurally, the modified MXene is a wrinkled three-dimensional structure, which is not only conducive to the penetration of the electrolyte, but also increases the contact area between LFP and the surface of the MXene material; In terms of performance, the electrochemical performance of the composite material prepared by the modified MXene is more excellent, and its low-temperature performance is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0045] Figure 1 Schematic diagram of the preparation process of LFP / MXene / C materials;
[0046] Figure 2 XRD patterns of MXene materials prepared with different intercalants;
[0047] Figure 3 The SEM images of the prepared MXene materials; (a, b) use TMAOH as an intercalation agent for intercalation, and (c, d) are MXene sheets obtained by peeling after intercalation;
[0048] Figure 4 XRD patterns of LFP / MXene composites with different MXene contents;
[0049] Figure 5 Raman images of MXene, LFP and LFP / MXene-7 materials;
[0050] Figure 6SEM images of the prepared materials: (a, b) LFP; (c, d) LFP / MXene-1; (e, f) LFP / MXene-3; (g, h) LFP / MXene-5; (i, j) LFP / MXene-7; (k, i) LFP / MXene-10;
[0051] Figure 7 Electrochemical performance test diagram of LFP / MXene composites prepared with different MXene contents; (a) first charge and discharge at 0.1C; (b) cycle performance at a current density of 0.1C; (c) rate performance;
[0052] Figure 8 CV diagrams of LFP / MXene composites with different MXene contents;
[0053] Fig. 9 The AC impedance test results of LFP and LFP / MXene-7 materials; (a) AC impedance diagram of LFP and LFP / MXene-7 materials; (b) corresponding Z′-ω -1 / 2 curve;
[0054] Fig.10 XRD patterns of LFP / MXene / C composites prepared at different carbonization temperatures;
[0055] Fig.11 Raman images of LFP and LFP / MXene / C-700 materials;
[0056] Fig.12 XPS graph of LFP / MXene / C-700 material; (a) survey; (b) C 1s; (c) Fe 2p; (d) Ti 2p;
[0057] Fig.13 SEM images of LFP / MXene / C composites prepared at different carbonization temperatures; (a, b) correspond to a calcination temperature of 650°C, (c, d) correspond to a calcination temperature of 700°C, and (e, f) correspond to a calcination temperature of 750°C;
[0058] Fig.14 Element distribution diagram of LFP / MXene / C-700 material;
[0059] Fig.15 TEM image of LFP / MXene / C-700 material;
[0060] Fig.16 The first charge and discharge curves of LFP / MXene / C composites prepared at different carbonization temperatures;
[0061] Fig.17 Schematic diagram of the rate performance of LFP / MXene / C composites prepared at different carbonization temperatures;
[0062] Fig.18 Cycling performance of LFP / MXene / C composites prepared at different carbonization temperatures at 0.1C current density
[0063] Fig.19 CV curves of LFP / MXene / C composites prepared at different carbonization temperatures;
[0064] Fig. 20 (a) AC impedance diagram of LFP / MXene / C composites prepared at different carbonization temperatures; (b) Corresponding Z′-ω -1 / 2 curve;
[0065] Fig.21 XRD patterns of LFP / MXene / C composites prepared with different carbonization times;
[0066] Fig. 22 SEM images of LFP / MXene / C composites prepared at different carbonization times; (a, b) LFP / MXene / C-4h; (c, d) LFP / MXene / C-6h; (e, f) LFP / MXene / C-8h;
[0067] Fig.23 The first charge and discharge curves of LFP / MXene / C composites prepared at different carbonization times;
[0068] Fig.24 The rate performance of LFP / MXene / C composites prepared at different carbonization times;
[0069] Fig.25 The cycling performance of LFP / MXene / C composites prepared at different carbonization times at a current density of 0.1C;
[0070] Fig.26 CV curve of LFP / MXene / C-6h material;
[0071] Fig. 27 (a) The first charge and discharge curves of LFP / MXene / C composite materials at different current densities at -20°C; (b) The rate performance at current density from 0.1C to 1C; (c) The cycle performance at 1C.
[0072] Fig.28 CV curves of LFP / MXene / C materials: (a) different temperatures; (b) -20 °C;
[0073] Fig.29SEM images of m-MXene samples prepared with different amounts of melamine added: (a, b) m-MXene-1; (c, d) m-MXene-3; (e, f) m-MXene-5; (g, h) m-MXene-7; (I, k) m-MXene-10;
[0074] Fig.30 XRD patterns of LFP, m-MXene and LFP / m-MXene / C materials;
[0075] Fig.31 It is the SEM image of LFP / m-MXene / C material;
[0076] Fig.32 Electrochemical performance test of LFP / m-MXene / C material; (a) cycle performance at 1C; (b) rate performance;
[0077] Fig.33 This is the CV curve of LFP / m-MXene / C material. DETAILED DESCRIPTION
[0078] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0079] Example 1
[0080] This example investigates the effect of different MXene contents on LFP / MXene composites
[0081] (I) Preparation of MXene
[0082] First, weigh 3g of Ti3AlC2 powder and slowly add it to a polytetrafluoroethylene beaker containing 30ml HF (40%) solution several times. Etch it with magnetic stirring for 24h at room temperature to allow HF to fully react with Ti3AlC2. After the reaction is completed, centrifuge and wash at a speed of 3500rpm until pH>6, and then dry it at 80℃ in vacuum for 12h to obtain Ti3C2 material. Weigh 1g of Ti3C2 material and add it to a beaker containing 10ml TMAOH and stir it at room temperature for 24h. After the end, centrifuge it at 5000rpm for 5min, collect the resulting precipitate, then ultrasonicate it for 2h, and then collect the supernatant at 4000rpm for 5min (3-5 times). Recorded as T-Ti3C2. The present invention finds that the etching time has a certain influence on the preparation of MXene materials. If the time is too short, it cannot be completely etched. If the etching time is too long, the structure of the MXene material will be destroyed to a certain extent due to the presence of the etchant. When the etching time is 24h, the Ti3C2 material obtained is in the shape of a two-dimensional accordion with a smooth surface. When TMAOH is used as an intercalation agent for 24h, the interlayer spacing of MXene is larger, and more thin Ti3C2 nanosheets are peeled off from the MXene material. The electrochemical performance of the obtained MXene material was tested, and the results showed that the electrochemical performance of the MXene material after etching was enhanced. Its first reversible specific capacity was 242.2mAh g -1 , the Coulomb efficiency in the first week was 50.2%. Figure 2 XRD patterns of MXene materials prepared with different intercalation agents (D in D-Ti3C2 stands for DMSO); Figure 2 As shown, the position of the characteristic peak corresponding to (002) of the MXene material treated with TMAOH is smaller. According to the Bragg equation, it can be concluded that the interlayer spacing of the material is larger at this time. Figure 3 This is the SEM image of the processed MXene material. It can be clearly observed in the figure that when TMAOH is used as an intercalation agent, more thin Ti3C2 nanosheets can be peeled off from the MXene material. This is consistent with the results of XRD.
[0083] (II) Preparation of LFP / MXene composites
[0084] In this experiment, the LFP / MXene composite material was prepared by solvothermal method. The specific scheme is as follows: LiOH·H2O, FeSO4·7H2O and H3PO4 were selected as lithium source, iron source and phosphorus source respectively according to the stoichiometric ratio of 3:1:1.
[0085] First, weigh 0.75g of LiOH·H2O and add it to a beaker containing 30ml of ethylene glycol, and stir mechanically until it is completely dissolved; then slowly add 0.69g of H3PO4 to the beaker and stir evenly to obtain solution A. Take 0.07g of accordion-shaped T i3 C2 (i.e., the MXene prepared above) and 1.66g FeSO4·7H2O were added to a beaker containing 40ml ethylene glycol, and ultrasonic dispersion was performed for 30min to obtain solution B. Solution B was added dropwise to solution A and stirred at room temperature for 10min. The obtained dark green solution was transferred to a 100ml hydrothermal reactor and hydrothermally reacted at 180℃ for 10h. After the reaction, the obtained product was washed three times with deionized water and ethanol respectively by centrifugation, and then vacuum dried at 80℃ for 12h to obtain the product LiFePO4 / MXene, which was recorded as LFP / MXene-7.
[0086] In order to explore the effect of Ti3C2 addition on the composite material, the addition amount of Ti3C2 was changed to 0, 0.01g, 0.03g, 0.05g and 0.10g respectively. According to the above steps, LFP, LFP / MXene-1, LFP / MXene-3, LFP / MXene-5, LFP / MXene-7 and LFP / MXene-10 were obtained.
[0087] The structure of LFP / MXene composites prepared with different MXene contents was analyzed. Figure 4 As shown in the figure, the XRD spectrum of lithium iron phosphate (LiFePO4) material prepared by solvothermal method shows a sharp and complete peak shape, and the diffraction peak of the material is consistent with the position of the diffraction peak of the olivine-type LiFePO4 standard card (JCPDS: 40-1499, Pnma). In addition, there are no other impurity peaks in the spectrum, proving that the prepared LiFePO4 material is a pure phase structure. For LFP / MXene composite materials, the diffraction peaks of LiFePO4 (011), (111) and (131) crystal planes can be observed, and the diffraction peak of Ti3C2 material (002) crystal plane can be observed. Prove the successful preparation of LFP / MXene composite materials. According to the XRD spectrum results, as the MXene content increases, the peak of Ti3C2 material corresponding to the (002) crystal plane in the composite material becomes stronger.
[0088] In order to further analyze the interaction between LFP and MXene, Raman spectroscopy analysis was performed on MXene, LFP and LFP / MXene-7 materials. The results are as follows Figure 5 According to the test results, in the Raman spectrum of pure MXene materials, the -1A sharp peak appears at 203 cm-1, which corresponds to the characteristic peak of the layered Ti3C2MXene material. -1 and 233cm -1 The peak at corresponds to the Fe 2+ The stretching vibration of LFP / MXene composite material is analyzed. The characteristic peaks of MXene can be seen in its Raman spectrum. 2+ The characteristic stretching vibration of LFP / MXene can also be observed, proving the successful composite of the two materials. This result is consistent with the XRD result, further confirming the successful preparation of LFP / MXene composites.
[0089] The morphology of LFP / MXene composites prepared with different MXene contents was analyzed. The SEM images of the prepared LFP, LFP / MXene-1, LFP / MXene-3, LFP / MXene-5, LFP / MXene-7 and LFP / MXene-10 materials are shown in Figure 2. Figure 6 shown. Figure 6 a and 6b show the nano-LFP particles prepared by the solvothermal method, whose particle size is about 100-200 nm and the particle size distribution is uniform. Figure 6 c and 6e are scanning electron microscope images of LFP / MXene-1 and LFP / MXene-3 materials, respectively. In the figure, it can be seen that the nano-LFP particles are tightly anchored on the surface of the layered MXene material. Due to the low content of MXene, a large amount of nano-LFP is only coated on the outer surface of the MXene material, making the microscopic morphology of the composite material not obvious. As the MXene content increases, the morphology of the LFP / MXene composite material becomes more obvious. When the MXene content is 7% ( Figure 6 i), by Figure 6 i It can be clearly observed that nano-LFP particles grow on the surface, side and interlayer of the accordion-shaped MXene material, forming a porous hierarchical structure. On the one hand, the appropriate layered structure can effectively alleviate the agglomeration of nano-LFP particles, and the accordion-shaped MXene can also provide a fast ion-electron conductive channel, accelerating the rapid transportation of electrons and lithium ions; on the other hand, the nano-LFP particles grow in situ between the MXene layers, forming a porous hierarchical conductive network similar to "point-surface-point". This structure is not only conducive to increasing the contact area between the material and the electrolyte and promoting the rapid transfer of ions, but also provides more active sites for redox reactions, thereby further improving the material's cycle stability and high-rate performance. Figure 6k is the SEM image of the composite material when the MXene content is 10%. As the MXene content increases, the nano-LFP particles are no longer tightly distributed in the MXene material. Due to the chemical energy on the surface of the material, the MXene material is more likely to self-stack together, resulting in a weakened binding energy between the LFP particles and the MXene. At this time, the diffusion of electrons and lithium ions will also be weakened. Therefore, the appropriate MXene content is conducive to building the best porous structure, inhibiting the aggregation of particles, and thus improving the electrochemical performance.
[0090] The electrochemical properties of LFP / MXene composites prepared with different MXene contents were tested. Figure 7 Electrochemical performance tests of LFP / MXene composites prepared with different MXene contents. Figure 7 Figure a shows the first charge and discharge curves of different materials at a current density of 0.1C. It can be seen from the figure that both the prepared LFP / MXene composite material and the pure phase LFP material have a charge and discharge platform, proving that the introduction of MXene does not change the charge and discharge reaction of LFP. At the same time, the addition of MXene makes the charge and discharge voltage difference smaller, that is, the porous hierarchical structure constructed by LFP and MXene provides more active sites and faster lithium ion transfer channels, reducing the polarization of the material and improving the utilization of the active material. For the solvothermally prepared nano-LFP material, its first discharge specific capacity is only 112.8mAh g -1 Compared with pure LFP material, the first discharge capacity of LFP / MXene composite material increased. When the MXene content was 7%, the composite material had a better discharge capacity of 143.4 mAh g -1 .
[0091] Figure 7 b is the cycle performance test of different materials at a current density of 0.1C, and the voltage range is 2.5-4.2V. It can be seen from the figure that for LFP, LFP / MXene-1, LFP / MXene-3, LFP / MXene-5, LFP / MXene-7 and LFP / MXene-10 materials, after 100 cycles, their reversible specific capacities are 113.6mAh g -1 , 121.1mAh g -1 、129.0mAh g -1 , 134.7mAh g -1 , 141.1mAh g -1 and 126.2mAh g -1 The test results show that the LFP / MXene-7 material has a more excellent cycle performance, and its capacity retention rate after 100 cycles is 96.0%.
[0092] Rate performance tests of different materials such as Figure 7 c. It can be clearly seen in the figure that the rate performance of the material is not effectively improved when the MXene content is 1% and 3%. With the increase of MXene content, the cycle stability of LFP / MXene composite material is improved. LFP / MXene-7 material shows better rate performance, and its average specific capacity at current density of 0.1C, 0.2C, 0.5C, 1C and 5C is 138.9, 133.6, 119.9, 108.5 and 98.7 mAh g -1 When the current density returned to 0.1C, the reversible capacity stabilized at 136.9 mAh g -1 , the capacity recovered to 98.5% of the original, which is much higher than the rate performance of pure phase LFP.
[0093] Figure 8 The cyclic voltammetry test of LFP / MXene composites with different MXene contents was performed. Figure 8 As shown in Figure 2, each material has a pair of redox peaks on its CV curve, which corresponds to Fe 2+ / F 3+ Charge and discharge reaction of redox couple. LFP / MXene-5, LFP / MXene-7 and LFP / MXene-10 have more symmetrical and sharp redox peaks, and their potential difference is also smaller, indicating that the electrochemical performance of these three materials is better. Among them, when the MXene content is 7%, its redox peak is more symmetrical, and at this time it has the smallest potential difference (0.24V), and the polarization is smaller, so its lithium ion diffusion rate is faster and the electrochemical performance is the best. This result shows that layered MXene can provide a faster lithium ion transfer channel for the electrochemical reaction of LFP material. At the same time, the porous hierarchical conductive network formed by it and LFP also increases the contact area between the material and the electrolyte, accelerates the rapid transfer of ions, and provides more active sites for redox reactions, further improving the electrochemical performance of the material.
[0094] Fig. 9 This is the AC impedance test of LFP and LFP / MXene-7 materials. The AC impedance diagram of each electrode was obtained by simulation using Zview software, as shown in Fig. 9 As shown in a. As can be seen from the figure, LFP / MXene-7 has the smallest semicircle, that is, the charge transfer impedance is the smallest, indicating that the introduction of MXene promotes the transfer of charge during the electrochemical reaction, so LFP / MXene-7 exhibits more excellent electrochemical performance. At the same time, the measured data were fitted using Zview software to obtain the fitting values of Rs and Rct. The fitted impedance real part (Z') is related to ω -1 / 2 The relationship curve is as follows Fig. 9b. The Li of the two materials is calculated + The ion diffusion coefficient results are shown in Table 1.
[0095] Table 1 Impedance spectra parameters and Li of LFP and LFP / MXene-7 materials + Ion diffusion coefficient
[0096] Samples <![CDATA[R s (Oh)]]> <![CDATA[R ct (Oh)]]> <![CDATA[D Li+ (cm 2 s -1 )]]> LFP 2.6 118.1 <![CDATA[1.98×10 -15 ]]> LFP / MXene-7 2.3 65.7 <![CDATA[2.19×10 -15 ]]>
[0097] From the data in the table, it can be seen that the ohmic internal resistance of LFP and LFP / MXene-7 is 2.6Ω and 2.3Ω respectively, while the electrochemical impedance R ct The results show that the LFP / MXene-7 material has a smaller electrochemical impedance value, proving that the addition of MXene promotes the rapid transfer of internal charges in the material and improves the Li + The transfer speed of ions. By calculation, the Li + The ion diffusion coefficient is greater than that of LFP. + The ion diffusion coefficient further confirms that the porous hierarchical structure of the composite material can provide more active sites, achieve faster lithium ion transfer channels, and thus improve the electrochemical performance.
[0098] Example 2
[0099] This example investigates the effect of different carbonization temperatures on the LFP / MXene / C composite material
[0100] In this example, LFP / MXene-7 material is selected as a precursor and a carbon layer is coated on its surface to further improve the conductivity of the material and explore the effect of different calcination temperatures on the material properties.
[0101] (I) Preparation of LFP / MXene / C
[0102] 0.1g of dopamine hydrochloride was dispersed in a beaker containing 50ml of deionized water, and then 0.5g of the prepared LFP / MXene material was added, and the mixture was stirred at 90℃ for 6h. After the reaction, the mixture was centrifuged, washed and dried, and a certain amount of the dried product was weighed and transferred to a porcelain boat, which was placed in a tubular furnace and calcined at 700℃ for 6h under Ar atmosphere to obtain LFP / MXene / C material, which was recorded as LFP / MXene / C-700.
[0103] By keeping the calcination time unchanged and changing the carbonization temperature to 650°C and 750°C, different composite materials were obtained, which were recorded as LFP / MXene / C-650 and LFP / MXene / C-750.
[0104] The structure of LFP / MXene / C composites prepared at different carbonization temperatures was analyzed. Fig.10 As shown. As can be seen from the figure, the diffraction peaks of LFP / MXene / C-650, LFP / MXene / C-700 and LFP / MXene / C-750 materials do not have obvious peak shifts compared to nano-LFP, proving that the introduction of C in the composite material does not lead to changes in the material structure. For the LFP / MXene / C composite material, there is no sharp C peak, but a broad peak at around 20°, indicating that the C obtained by calcining dopamine hydrochloride as a carbon source is amorphous. With the change of carbonization temperature, the intensity of the C peak is also different. When the carbonization temperature is 700°C, the intensity of the broad peak is more obvious.
[0105] In Example 1, by comparing the Raman spectra of LFP and MXene, it has been proved that the LFP / MXene composite material can be prepared by the solvothermal method. In order to further improve the conductivity of the LFP / MXene composite material, the carbon coating was performed on it and Raman analysis was performed. The results are as follows: Fig.11 As shown in the figure, the LFP / MXene / C-700 material has a -1 and 1598cm -1 Two obvious characteristic peaks appear at the surface of the carbon layer, which correspond to the D peak and the G peak, respectively, proving the existence of the carbon layer. D represents the defects of graphite carbon, reflecting its disordered structure. G represents the offset model of graphite carbon, reflecting its ordered structure. The ratio between the two represents the disorder of the carbon on the surface of the material. The larger the ratio, the higher the disorder. For LFP / MXene / C-700 material, through calculation, its I D with I G The ratio is 1.03, which proves that the carbon layer coated on the surface of the composite material is amorphous. This result is consistent with the result of XRD, proving that the carbon layer is successfully coated.
[0106] In order to further analyze the elemental composition and valence state of the composite material surface, the LFP / MXene / C-700 material was tested by XPS. The results are shown in Fig.12 As shown. Fig.12 As shown in a, the XPS spectrum of the composite material has six peaks at binding energies of 711, 531, 458, 284, 190, 133 and 56 eV, which correspond to Fe 2p, O 1s, Ti 2p, C 1s, P 2s, P2p and Li 1s orbitals, respectively. Fig.12) after fitting, it was found that it can be divided into three spectral peaks, located at 284.8 eV, 286.8 eV and 289.4 eV, corresponding to C–C, C–O–C and C–O=C bonds, respectively. Fig.12 c corresponds to the high-resolution XPS spectrum of the Fe element, which can be divided into two broad peaks. The broader peak at the binding energy of 723.4 eV is the 2p3 / 2 orbital of the Fe element, while the corresponding peak at the binding energy of 710.2 eV is the 2p 1 / 2 orbital of the Fe element. This result shows that the valence state of Fe in the composite material is +2, which is consistent with the valence state of Fe in LFP. The XPS spectrum of the Ti element is shown in Figure 2. Fig.12 As shown in Figure d, after fitting, the 2p3 / 2 orbital of the Ti element and the 2p1 / 2 orbital of the Ti element can be divided into four peaks, corresponding to +3 and +4 valence Ti, respectively. The reason for their formation is the lattice defects on the surface of the MXene material. In addition, the Li 1s peak corresponding to the binding energy of 56eV and the P 2p and P 2s peaks corresponding to 133 and 190eV in the XPS spectrum of the LFP / MXene / C-700 material originate from the Li and P elements of the LFP. The strong O1s peak with a binding energy of 531eV corresponds to the PO4 3- , proving that neither LFP nor Ti3C2 materials in the composite material have changed.
[0107] The morphology of LFP / MXene / C composites prepared at different carbonization temperatures was analyzed. In order to explore the effect of carbonization temperature on material properties, LFP / MXene / C materials with different carbonization temperatures were prepared and SEM tests were performed. The results are shown in the figure. Fig.13 As shown. Fig.13 a and 13b, it can be clearly observed that dopamine hydrochloride forms a coating layer on the surface of nano-LFP particles after high-temperature decomposition. However, due to the low calcination temperature, the carbon layer does not completely inhibit the agglomeration of nano-LFP particles. When the calcination temperature is 700℃ ( Fig.13 c, Fig.13 d), it can be seen that the LFP particles can still maintain their original morphology and are evenly dispersed between the layers and sides of the MXene, effectively inhibiting the re-accumulation of nano-LFP particles and MXene during the high temperature process, thereby improving the electronic conductivity and electrochemical properties of the material. As the calcination temperature increases, the agglomeration of nano-LFP particles becomes more serious. At the same time, due to the self-accumulation of MXene materials under high temperature conditions, the nano-LFP particles are detached from the MXene layers, destroying the original structure of the material, thereby affecting the electrochemical properties of the material.
[0108] In order to further determine the content of each element in the composite material, EDS test was carried out on LFP / MXene / C-700 material, such as Fig.14As shown. C, Ti, Fe, P and O elements are evenly distributed on the surface of the composite material, indicating that the nano-LFP particles grow evenly on the sides and between the layers of MXene. The specific element content analysis is shown in Table 2. The atomic proportion of the Ti element is 18.46%, the atomic proportion of the C element is 12.89%, and the atomic ratio of Ti to C is close to 3:2. At the same time, it can be concluded that the atomic ratio of Fe, P, and O elements is about 1:1:4, which proves that the obtained material is a pure material of Ti3C2 and LiFePO4, which corresponds to the analysis results of XRD and XPS.
[0109] Table 2 Atomic content of LFP / MXene / C-700 materials
[0110] Element Weight / % Atom / % C 6.39 12.89 Ti 32.48 18.46 Fe 21.05 10.66 P 12.02 12.42 O 28.06 45.57
[0111] In order to further observe the morphology and microstructure of the prepared LFP / MXene / C-700 material, transmission electron microscopy was performed. The results are as follows Fig.15 shown. Fig.15 In a, it can be observed that the composite material is composed of layered MXene and nano-sized LFP particles. The nano-LFP particles grow evenly between the layers of MXene, forming a "surface-point-surface" porous hierarchical conductive structure, which is consistent with the results of the SEM image. Fig.15 b is a high-resolution transmission electron microscope image, which shows the high crystallinity of LFP and MXene materials. The lattice spacing of 0.45nm corresponds to the (001) crystal plane of LFP material. The lattice spacing of 0.96nm corresponds to a single layer of MXene material. At the same time, an amorphous carbon layer can be observed on the surface of LFP particles, proving that the carbon layer is successfully coated on the surface of LFP material. The presence of the carbon layer can reduce the agglomeration of particles and the contact resistance between particles, and further improve the conductivity of LFP material.
[0112] Electrochemical tests were performed on LFP / MXene / C composites prepared at different carbonization temperatures. Fig.16 As shown in the figure, the LFP / MXene / C prepared at different carbonization temperatures was subjected to constant current charge and discharge tests with a current density of 0.1C. The test results show that the first charge and discharge curves of all materials show a charge and discharge platform within 3.3-3.5V, which corresponds to Fe 3+ / Fe 2+The redox electron pairs indicate the lithium insertion and removal process of lithium ions. Compared with the pure phase LFP material, the charge and discharge platform of the carbonized material is extended and more obvious, proving that the reaction kinetics of the carbonized LFP / MXene / C composite material is better. Compared with the pure phase LFP material, the first discharge specific capacity of the LFP / MXene / C material prepared at different carbonization temperatures is improved, which is 144.9mAh g -1 , 152.4mAh g -1 and 148.1mAh g -1 .
[0113] Fig.17 This is the rate cycling diagram of the composite material. It can be seen from the figure that the prepared LFP / MXene / C-700 material has the best performance, and its first reversible specific capacity at a current density of 0.1C is 151.5 mAh g -1 The first coulombic efficiency is 97.6%, which is better than the reversible specific capacity of other materials at carbonization temperature. The average reversible capacity at current densities of 0.2C, 0.5C, 1C and 5C is 143.2, 130.2, 117.8 and 107.2 mAh g, respectively. -1 When the current density is restored to 0.1C, the reversible specific capacity can still reach 148.5 mAh g -1 , the capacity recovered to 98.0% of the original.
[0114] The cycling performance test of LFP / MXene / C composites prepared at different carbonization temperatures at a current density of 0.1C is shown in the figure. Fig.18 The test results show that the LFP / MXene / C material prepared under 700℃ carbonization conditions has the best cycle performance, and its first discharge capacity is 156.3mAh g -1 The coulombic efficiency of the first cycle is 97.2%. After 100 cycles, the discharge capacity can be maintained at 149.3 mAh g -1 The capacity retention rate is 95.5%. The reversible specific capacity of LFP / MXene / C-650 and LFP / MXene / C-750 materials reached 141.9 mAh g after 100 cycles. -1 and 144.9mAh g -1 , both higher than the reversible specific capacity of LFP.
[0115] In order to further analyze the reaction kinetics of LFP / MXene / C composites, the prepared composites were subjected to cyclic voltammetry tests with a voltage window of 2.5–4.2 V and a scan rate of 0.1 mV s -1 , the test results are as follows Fig.19As shown in the figure, it can be clearly observed that the prepared materials have symmetrical redox peaks, which correspond to the Fe 3+ / Fe 2+ Compared with the nano-LFP material, the redox peaks of the LFP / MXene / C composite material are sharper and more symmetrical, indicating that the reversibility of lithium ion insertion / extraction is enhanced and the reaction kinetics are also improved. At the same time, LFP / MXene / C-700 has a smaller polarization voltage (η=0.23V), proving that the conductivity of the material is better under this temperature condition, which is consistent with the cycle and rate test results.
[0116] In order to further study the electrode reaction kinetics of LFP and LFP / MXene / C composites, the prepared materials were subjected to EIS tests at a test frequency range of: 10 -2 ~10 -5 Hz, with an amplitude of 5mV. The results are as follows Fig. 20 shown. Fig. 20 a is the Nerquist plot of the prepared LFP, LFP / MXene / C-650, LFP / MXene / C-700 and LFP / MXene / C-750 materials under full charge state. The AC impedance curve of each material is composed of a semicircle and a slash, corresponding to the equivalent circuit diagram embedded in it: Among them, the intercept of the semicircle and the real part in the high-frequency region is the ohmic internal resistance, expressed as R s Indicated by; the diameter of the semicircle in the intermediate frequency region is the charge transfer impedance, expressed as R ct The curve in the low frequency region is the Warburg impedance, which is represented by W. The R s , R ct , the fitting value of the diffusion coefficient D. , the results are shown in Table 3.
[0117] Table 3 Impedance spectrum parameters and Li of LFP / MXene / C composites prepared at different carbonization temperatures + Ion diffusion coefficient
[0118] Samples <![CDATA[R Ω (Oh)]]> <![CDATA[R ct (Oh)]]> <![CDATA[D Li+ (cm 2 s -1 )]]> LFP 4.1 152.2 <![CDATA[8.51×10 -15 ]]> LFP / MXene / C-650 3.2 92.7 <![CDATA[1.89×10 -14 ]]> LFP / MXene / C-700 1.7 68.7 <![CDATA[1.48×10 -14 ]]> LFP / MXene / C-750 3.7 117.8 <![CDATA[1.55×10 -14 ]]>
[0119] In Table 3, the ohmic internal resistance of LFP, LFP / MXene / C-650, LFP / MXene / C-700 and LFP / MXene / C-750 materials are 4.1, 3.2, 1.7 and 3.7Ω respectively, and their electrochemical reaction internal resistance are 152.2, 92.7, 68.7 and 117.8Ω respectively. By comparison, LFP / MXene / C-700 material has smaller electrochemical transfer impedance and larger Li + The ion diffusion coefficient proves that the electrochemical performance of the composite material calcined at 700 °C is better.
[0120] Example 3
[0121] This example investigates the effects of different calcination times on the LFP / MXene / C composite material
[0122] Example 2 By exploring the carbonization time, it was found that 700°C was the optimal carbonization temperature. Therefore, this example selected 700°C as the carbonization temperature and studied the effect of carbonization time on the properties of the composite material. The carbonization temperature was changed for 4h, 6h and 8h, and the materials obtained after carbonization were recorded as LFP / MXene / C-2h, LFP / MXene / C-4h, and LFP / MXene / C-6h, respectively.
[0123] The structural analysis of LFP / MXene / C composites prepared with different carbonization times was carried out. Fig.21 The XRD diagrams of LFP / MXene / C composite materials prepared at different carbonization times. According to the test results, the broad peak of LFP / MXene / C-6h material is more obvious, proving that more amorphous carbon is converted from dopamine hydrochloride at this time. With the increase of carbonization time, the intensity of the broad peak does not increase, and due to the high-temperature calcination, the MXene material self-stacking occurs, the interlayer spacing of MXene becomes smaller, and the position of the characteristic peak corresponding to the (002) crystal plane shifts to the right. As a result, the porous structure formed by the LFP material and the MXene material is destroyed, which in turn affects the electrochemical properties of the material.
[0124] The morphology of LFP / MXene / C composites prepared with different carbonization times was analyzed. Fig. 22 SEM images of LFP / MXene / C materials prepared at different carbonization temperatures. Fig. 22 a and 22b, it can be observed that nano-LFP particles are anchored between the layers and on the surface of the MXene material, but due to the short carbonization time, the carbon layer on the surface of the composite material is not fully formed. As the carbonization time increases to 6 h, Fig. 22 As shown in Fig. 22d, the size of LFP particles increases, and the carbon layer is evenly coated, which inhibits the agglomeration of LFP particles, allowing them to grow evenly in the structure of MXene materials, shortening the diffusion distance of lithium ions during the charge and discharge process, thereby improving the electrochemical performance of the material. Fig. 22 e and 22f show that when the carbonization time increases to 8h, the carbon layer will cover the entire LFP / MXene composite material, making the structure of the material no longer obvious. At the same time, due to the increase in calcination time, the self-stacking of the MXene material becomes more serious, and its interlayer spacing will decrease, destroying the accordion-like structure of MXene, causing some LFP particles to escape from its interlayers, and the fast channel for lithium ion diffusion is inhibited, thereby affecting the electrochemical properties of the material.
[0125] Electrochemical tests were carried out on LFP / MXene / C composites prepared with different carbonization times. Fig.23 The first charge and discharge curves of LFP / MXene / C-4h, LFP / MXene / C-6h and LFP / MXene / C-8h materials at a current density of 0.1C are shown. The test results show that the first charge and discharge curves of each material have a peak around 3.4V corresponding to Fe 3+ / Fe 2+ The charge and discharge platform of the redox electron pair. By comparison, it was found that the charge and discharge platform of the LFP / MXene / C-6h material was longer and the polarization voltage was smaller, proving that the reaction kinetics of the LFP / MXene / C composite material under this condition was more excellent. Compared with the other two materials, the LFP / MXene / C-6h material had a higher discharge specific capacity of 154.1 mAh g -1 . And its Coulomb efficiency is as high as 98.2%.
[0126] In order to further study the effect of carbonization time on the high-rate performance of the material, the prepared composite material was subjected to rate cycle tests, such as Fig.24 As shown in the figure, the prepared LFP / MXene / C-6h material has the best electrochemical performance, and its reversible specific capacity in the first week at a current density of 0.1C is 148.2 mAh g -1 The first-week coulombic efficiency is 98.6%. When the current density increases to 0.2C, 0.5C, 1C and 5C, the average reversible capacity can reach 138.2, 125.1, 114.9 and 102.2 mAh g, respectively. -1 When the current density returns to 0.1C, the reversible specific capacity can still reach 140.5 mAh g -1 , the capacity recovered to 94.8% of the original, which is much better than the composites prepared under other carbonization conditions.
[0127] Fig.25 The cycle performance test of LFP / MXene / C composite materials prepared with different carbonization times at a current density of 0.1C. The figure shows that the cycle specific capacity curves of each material tend to be flat, and when the carbonization time is 6h, the LFP / MXene / C-6h material has the best cycle performance, and its first discharge specific capacity is 151.8mAh g -1 The coulombic efficiency of the first cycle is 98.6%. After 100 cycles, the discharge capacity can be maintained at 150.1 mAh g -1The capacity retention rate is 98.8%. The reversible specific capacities of LFP / MXene / C-4h and LFP / MXene / C-8h materials after 100 cycles are 139.3 mAh g -1 and 131.7mAh g -1 .
[0128] Fig.26 The CV curve of the sample prepared with a carbonization time of 6 h is shown. The peaks at 3.30 V and 3.56 V in the first week of cyclic voltammetry test correspond to the Fe 3+ / Fe 2+ The redox reaction of LFP / MXene / C-6h is sharp, which proves that the electrochemical reaction kinetics of LFP / MXene / C-6h material is good. This result is consistent with the charge and discharge platform of the first week. As the cycle progresses, the position of the redox peak remains basically unchanged, and the peak shape does not shift significantly. In addition, the redox peak increases, indicating that the material has good cycle stability and Li + The diffusion rate of ions is also improved.
[0129] Example 4
[0130] This example investigates the low temperature performance of LFP / MXene / C composites prepared under optimal conditions
[0131] In this embodiment, the material prepared with a MXene content of 7%, a carbonization condition of 700°C, and 6 hours was selected for low temperature performance test. The SWAY-001 electrolyte provided by SWAY Electronic Materials Co., Ltd. was used during the test.
[0132] This example focuses on testing the electrochemical properties of the material under low temperature conditions. The low temperature test of the LFP / MXene / C material is to conduct material charging and discharging, AC impedance and cyclic voltammetry tests in a -20°C constant temperature box.
[0133] Fig. 27 The electrochemical test results of LFP / MXene / C composite materials at -20℃. Fig. 27 As shown in a, the first discharge specific capacities of LFP / MXene / C materials at current densities of 0.1C, 0.2C, 0.5C, and 1C are 86.4, 72.1, 60.4, and 52.5 mAh g, respectively. -1 At 0.1C, its first discharge capacity can reach 56.6% of that at room temperature. Fig. 27 As shown in b, the average reversible capacities at current densities of 0.1C, 0.2C, 0.5C and 1C are 87.9, 74.9, 62.3 and 48.6 mAh g, respectively. -1When the current density is restored to 0.1C, the reversible specific capacity can still be restored to 84.0 mAh g -1 , capacity recovered to 95.5% of the original. Fig. 27 c shows the cycling performance test of LFP / MXene / C at a current density of 1C. According to the test structure, the reversible specific capacity of the material after 100 cycles is 46.9 mAh g -1 , the capacity retention rate is 99.1%.
[0134] In order to further analyze the kinetics of LFP / MXene / C materials under low temperature conditions, cyclic voltammetry tests were performed with a scan rate of 0.1 mV s -1 The results are as follows Fig.28 shown. Fig.28 a is a comparison of the fifth week CV curves of LFP / MXene / C materials under room temperature and -20℃ test conditions. It can be seen from the figure that a pair of redox peaks can be observed under both conditions. However, the potential difference under room temperature is 0.243V, while under low temperature conditions, due to the slowdown of reaction kinetics, the redox peak potential difference increases to 0.438V at low temperatures, and the corresponding peak current is half of that under room temperature conditions, proving that under low temperature conditions, Li + The embedding and extraction speed of ions in the material slows down, and the polarization of the material increases. As the cycle progresses, the redox peak of the composite material gradually increases, proving that the low-temperature performance of the material has improved. This provides new ideas for the use of lithium iron phosphate batteries under low-temperature conditions and greatly broadens the application range of lithium iron phosphate materials.
[0135] Example 5
[0136] This example investigates the preparation and performance of a modified MXene and LFP composite material; a modified MXene material is composited with LFP and carbon-coated to obtain an LFP / m-MXene / C material.
[0137] (I) Preparation of modified MXene (the material is a few-layer corrugated material)
[0138] Disperse 10g of melamine in a beaker containing 20ml of anhydrous ethanol and stir for 1h at room temperature. Then add 10ml of concentrated hydrochloric acid (HCl) and continue magnetic stirring for 1h. Centrifuge to remove excess solvent. After that, dry the obtained material in a vacuum oven at 80℃ to obtain H+-modified melamine, which is recorded as H+-Melamine.
[0139] 50 ml of 1 mg / ml MXene (Example 1) colloidal solution was measured and placed in a beaker, which was recorded as solution A; 0.25 g of H+-modified melamine was weighed according to the mass ratio of 1:5 and dissolved in 50 ml of 0.1 M dilute hydrochloric acid solution, which was recorded as solution B; solution B was slowly added to solution A. With the addition of solution B, it can be clearly observed that the MXene colloidal solution undergoes electrostatic flocculation. Stirring was continued at room temperature for 1 hour to allow the H+-modified melamine to be fully adsorbed in the structure of MXene. After the reaction was completed, the solution was filtered and washed with water to remove excess impurities, and freeze-dried to obtain black MXene-Melamine powder.
[0140] The MXene-Melamine powder obtained above was placed in a porcelain boat and kept at 550°C for 4 hours under a nitrogen atmosphere to obtain a modified MXene material, which was recorded as m-MXene-5.
[0141] Change H + The mass ratios of modified melamine to MXene are 1:1, 3:1, 7:1 and 10:1, and the other preparation conditions remain unchanged, thus obtaining modified MXene materials with different amounts of melamine added, which are respectively recorded as m-MXene-1, m-MXene-3, m-MXene-7 and m-MXene-10.
[0142] SEM images of m-materials prepared with different amounts of melamine added are shown in Figure 29. The Ti3C2MXene material after etching in Example 1 is accordion-shaped. Since the surface of the MXene material after etching has a large number of functional groups such as -OH, -O and -F, the MXene surface is negatively charged, and the electrostatic repulsion inside the material causes it to be stably dispersed in water. After adding H+-modified melamine, the two will be adsorbed together due to electrostatic effects and form a precipitate. At the same time, the H+-modified melamine present in the structure of the MXene material will decompose after high-temperature calcination in a nitrogen atmosphere, causing some amino groups to generate electrostatic effects on the MXene surface. As calcination proceeds, under the dual effects of the gas generated by high-temperature decomposition and surface energy, the layered MXene material will be peeled off, and at the same time, it will be bent in the three-dimensional direction to form an N-doped three-dimensional MXene modified material. Fig.29 As shown in Fig. 29b, due to the addition of H+-modified melamine, the monolayer Ti3C2 on the surface of the MXene material begins to fall off and shows a shrinkage trend; and as the amount of H+-modified melamine added increases, as shown in Fig.29As shown in Figures 29b and 29d, the interlayer spacing of MXene materials gradually expands. When the addition amount increases to 5:1, more wrinkled nanosheets can be observed. When the addition amount of melamine is greater than 7:1, the Ti3C2 nanosheets have obvious agglomeration phenomenon, which is due to the surface energy of ultra-thin Ti3C2 nanosheets.
[0143] (II) Preparation of LFP / m-MXene / C composites
[0144] First, weigh 0.75g of LiOH·H2O and add it to a beaker containing 30ml of ethylene glycol, and stir mechanically until it is completely dissolved; then slowly add 0.69g of H3PO4 to the above beaker and stir evenly to obtain solution A. Take 0.07g of modified Ti3C2 and add it to a beaker containing 40ml of ethylene glycol, ultrasonically disperse for 30min, then mechanically stir and add 1.66g of FeSO4·7H2O to obtain solution B. Solution A is added dropwise to solution B, and the reaction is stirred at room temperature for 30min. The obtained solution is transferred into a 100ml hydrothermal reactor and hydrothermally reacted at 180℃ for 10h. After the reaction, the obtained product is centrifuged and washed three times with deionized water and ethanol respectively, and then vacuum dried at 80℃ for 12h to obtain the product LiFePO4 / m-MXene, recorded as LFP / m-MXene.
[0145] 0.1g of dopamine hydrochloride was dispersed in a beaker containing 50ml of deionized water, and then the above product was added and stirred at 90℃ for 6h. After the reaction, it was centrifuged, washed and dried. A certain amount of the dried product was weighed and transferred to a porcelain boat, which was placed in a tube furnace and calcined at 700℃ for 6h under Ar atmosphere to obtain LFP / m-MXene / C material. The structure of LFP / m-MXene / C material was analyzed. Fig.30 The XRD diagrams of LFP, m-MXene and LFP / m-MXene / C materials are shown in the figure. As can be seen from the figure, compared with the modified MXene material, the characteristic peak corresponding to the (002) crystal plane of the prepared composite material shifts to the left by 0.66°, indicating that the introduction of LFP nanoparticles increases the interlayer spacing of the MXene material. At the same time, the characteristic peak of LFP in the composite material can also be clearly observed, proving that the scheme for preparing composite materials is feasible.
[0146] The morphology of LFP / m-MXene / C material was analyzed. The SEM images of the prepared LFP / m-MXene / C were analyzed. Fig.31 As shown; it can be clearly observed in the figure that nano-LFP particles grow on the surface of the wrinkled MXene material, and are evenly distributed without aggregation.
[0147] The electrochemical performance of LFP / m-MXene / C material was tested. Fig.32 a is the cycle performance test of the prepared LFP / m-MXene / C material, and its current density is 1C. It can be clearly observed in the figure that the material has good cycle stability. Its first discharge specific capacity is 115.4mAh g -1 After 100 cycles, the reversible specific capacity can reach 113.0 mAh g -1 , the capacity retention rate can reach 97.9%.
[0148] Fig.32 b is the performance test of LFP / m-MXene / C material at different rates. The average specific capacities at current densities of 0.1C, 0.2C, 0.5C, 1C and 5C are 155.2, 143.1, 128.7, 120.6 and 109.2 mAh g, respectively. -1 When the current density is restored to 0.1C, the average specific capacity can still be restored to 151.7 mAh g -1 , with excellent rate performance.
[0149] Cyclic voltammetry test was performed on LFP / m-MXene / C material, and the results are as follows: Fig.33 As shown. According to the test results, the redox peaks of the LFP / m-MXene / C material are located at 3.54 V and 3.31 V. Starting from the second week, the redox peak current of the CV curve also increased, and the curves had good overlap, proving that the material has excellent cycle stability.
[0150] In summary, the present invention successfully prepared LFP / MXene / C composite materials by solvothermal method, and the materials prepared by the present invention have a porous hierarchical conductive network structure similar to "point-surface-point". This structure can greatly improve the conductivity of the material. At the same time, the large specific surface area and pores can provide more diffusion channels to ensure sufficient immersion of the electrolyte and sufficient lithium ion transfer; as the LiFePO4 particles decrease, the immiscible area of the LiFePO4 / FePO4 two phases will also become smaller, the specific capacity will increase, and at the same time, the agglomeration of nano-LiFePO4 particles and the volume change during charging and discharging will be alleviated, which will effectively further improve the high rate performance, cycle stability and low temperature performance of the material.
[0151] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A LFP / MXene / C composite material, characterized in that: The composite material has a "point-surface-point" porous hierarchical conductive network formed by in-situ growth of nano LFP particles between accordion-shaped MXene layers; nano LFP particles are also grown on the surface and side of the MXene material, and the LFP / MXene surface and the LFP particle surface are coated with a carbon layer; the preparation of the LFP / MXene / C composite material is to firstly synthesize the LFP / MXene material by solvent thermal synthesis, and further coat the carbon coating to obtain the LFP / MXene / C composite material; the specific steps are as follows: S1, lithium source, phosphorus source, MXene and iron source undergo hydrothermal reaction in the presence of a solvent to obtain LFP / MXene material; S2, adding LFP / MXene material to the carbon source solution, stirring and reacting at a constant temperature; calcining the reaction product under an inert atmosphere to obtain LFP / MXene / C material; In step S1, the MXene is prepared by a method comprising the following steps: A1, Ti3AlC2 powders are added to HF solution and etched under magnetic stirring at room temperature; after the reaction is completed, centrifugal washing is performed until pH>6, and vacuum drying is performed to obtain Ti3C2 material; each gram of Ti3AlC2 powder corresponds to 10ml of 40% HF solution; A2. Add 10 ml of TMAOH per gram of Ti3C2 material and stir at room temperature for 12-24 hours. Centrifuge, collect the precipitate, sonicate, and centrifuge to collect the supernatant to obtain MXene.
2. The LFP / MXene / C composite material according to claim 1, characterized in that According to the stoichiometric ratio, LiOH·H2O, FeSO4·7H2O and H3PO4 are selected as lithium source, iron source and phosphorus source respectively; the solvent includes one or two of ethylene glycol and polyethylene glycol.
3. The LFP / MXene / C composite material according to claim 1, characterized in that Step S1 specifically includes: S1-1, a lithium source is dissolved in ethylene glycol, and a phosphorus source is added to obtain solution A; S1-2, MXene and iron source are dispersed in ethylene glycol to obtain solution B; S1-3. Solution B is added dropwise into solution A, and LFP / MXene material is obtained by hydrothermal reaction.
4. The LFP / MXene / C composite material according to claim 1, characterized in that In step S1, the mass ratio of MXene to iron source is 0.01-0.10:1.66; the temperature of the hydrothermal reaction is 160-200°C, and the time is 8-12h.
5. The LFP / MXene / C composite material according to claim 1, characterized in that The MXene is a modified MXene, which is prepared by a method comprising the following steps: B1. Melamine is dispersed in anhydrous ethanol, stirred at room temperature, concentrated hydrochloric acid is added, stirring is continued, and excess solvent is removed by centrifugation. The obtained material is vacuum dried to obtain H+-modified melamine, which is recorded as H+-Melamine; B2. Take 1 mg / ml MXene colloidal solution, recorded as solution A; H+-modified melamine is dissolved in 0.1 M dilute hydrochloric acid solution, recorded as solution B; Solution B was slowly added to solution A, and stirred at room temperature to allow H+-modified melamine to be fully adsorbed into the structure of MXene. The solution was filtered, washed with water, and freeze-dried to obtain black MXene-Melamine powder. B3. The MXene-Melamine powder is kept at 500-600° C. for 2-6 hours under a nitrogen atmosphere to obtain a modified MXene material.
6. The LFP / MXene / C composite material according to claim 1, characterized in that In step S2, the carbon source solution includes 0.2 g / ml dopamine hydrochloride aqueous solution, ethylene glycol or ascorbic acid; the inert atmosphere includes argon or argon-hydrogen mixed gas; the temperature of the constant temperature stirring reaction is 90°C, and the reaction time is 6-8h; the calcination temperature is 650-750°C, and the calcination time is 4-8h.
7. Use of the LFP / MXene / C composite material according to any one of claims 1 to 6 in preparing a positive electrode for a lithium ion battery.
Citation Information
Patent Citations
Negative electrode composite material Sn / MXene@C and preparation method thereof
CN110429270A
Metal doped and Mxene coated double modified lithium iron phosphate composite material, and preparationmethodand application
CN110589793A